2020
DOI: 10.1177/0739986320927512
|View full text |Cite
|
Sign up to set email alerts
|

Latina Mothers’ Awareness of Their Children’s Exposure to Community Violence

Abstract: This study examines (a) the degree of agreement between mother-reported child community violence exposure and children’s self-reports and whether agreement changes over time; (b) whether child gender is associated with mother-child agreement; and (c) whether greater mother-child agreement is concurrently and longitudinally associated with children’s psychological well-being. We conducted secondary data analyses using longitudinal data with a socioeconomically diverse sample of 287 Latino adolescents ( MageW2 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…First, our study showed that parent-adolescent dyads from low-income families in Singapore had incongruent perceptions of neighborhood safety, in line with past research (Ceballo et al, 2001;Lewis et al, 2012). Previous studies had shown that parents tended to underestimate their children's exposure to community violence (Zimmerman & Farrell, 2013;Zimmerman & Pogarsky, 2011), especially as their children moved on to adolescence (Alers-Rojas et al, 2020). We observed a similar patternmost parents who had incongruent perceptions of neighborhood safety with their adolescent children perceived that their neighborhoods were safer than their children.…”
Section: Incongruent Perceptions Of Neighborhood Safety Among Parent-...supporting
confidence: 89%
See 1 more Smart Citation
“…First, our study showed that parent-adolescent dyads from low-income families in Singapore had incongruent perceptions of neighborhood safety, in line with past research (Ceballo et al, 2001;Lewis et al, 2012). Previous studies had shown that parents tended to underestimate their children's exposure to community violence (Zimmerman & Farrell, 2013;Zimmerman & Pogarsky, 2011), especially as their children moved on to adolescence (Alers-Rojas et al, 2020). We observed a similar patternmost parents who had incongruent perceptions of neighborhood safety with their adolescent children perceived that their neighborhoods were safer than their children.…”
Section: Incongruent Perceptions Of Neighborhood Safety Among Parent-...supporting
confidence: 89%
“…Past studies had shown that parents' underestimation of their children's exposure to community violence was associated with more child internalizing and externalizing behaviors (Zimmerman & Farrell, 2013;Zimmerman & Pogarsky, 2011), while greater parent-child agreement about community violence exposure was associated with fewer child externalizing problems (Alers-Rojas et al, 2020). As parent-child agreement on their perceptions of neighborhood safety and community violence exposure is a malleable protective factor, future studies could seek to explore the factors that contribute to a greater alignment in parent-adolescent perceptions of neighborhood safety, such as better parent-adolescent communication and parent-adolescent relationship closeness.…”
Section: Incongruent Perceptions Of Neighborhood Safety Among Parent-...mentioning
confidence: 99%
“…The studies examining the Latina women have addressed the following effects on motherhood: immigration, racism, community violence, poverty, as well as postpartum depression and anxiety (Alers-Rojas et al, 2020; Sampson et al, 2018; Straut-Eppsteiner, 2021; Vesely et al, 2019). Latina women often face blocks to help-seeking behaviors when postnatal mental health problems occur (Sampson et al, 2018).…”
Section: Research On Latina Motherhoodmentioning
confidence: 99%